Análise de recorrência da atividade interictal nas subregiões do hipocampo esclerótico humano na epilepsia mesial do lobo temporal - Araujo, Noemi dos Santos [UNIFESP] (2019)
The epileptiform-like activity patterns occurring in the sclerotic hippocampus with highest incidence are interictal-like events (II) and periodic ictal spiking (PIS). Previous investigations have shown that these activity patterns do not coexist in the same hippocampal subfield and are mainly classified according to their event rates. However, it is still unclear if there is specific information about the sclerotic substrate associated with these two types of epileptiform-like activity. Objective: To investigate II and PIS focusing on the evaluation of the spatiotemporal dynamics of these epileptiform-like activity patterns. Methods: We analyzed 35 electrophysiological data recorded in vitro from slices of 12 hippocampal specimens surgically resected from patients with pharmacoresistant temporal lobe epilepsy, by applying correlation approaches and recurrence analysis. Results: We found that different dynamical features characterize II and PIS activities. The II activity presents typical features of chaoticity with high stochasticity and periods of event acceleration/deceleration compared to PIS, whereas PIS presents higher regularity and determinism in relation to II. By comparing the epileptiform activity dynamics in each hippocampal subfield, it was possible to classify these regions into two different groups: (i) dentate gyrus and subiculum; and (ii) CA1-CA4. Conclusion: The results indicate that II and PIS have a completely different spatiotemporal dynamics, suggesting that these two types of epileptiform activity are signatures of distinct physical systems. Additionally, the differences in variability of event intervals and the different temporal markers for each hippocampal subfield suggest the occurrence of distinct dynamic processes in each one.